Transcriptional Changes in Chronic Rhinosinusitis with Asthma Favor a Type 2 Molecular Endotype Independent of Polyp Status - Gill, Amarbir S (J Asthma Allergy, 2021)
BACKGROUND: Data regarding the inflammatory profile of patients with asthma and chronic rhinosinusitis (CRS-A) with (CRSwNP-A) and without (CRSsNP-A) nasal polyposis remain limited. OBJECTIVE: Define and compare systemic transcriptional changes in patients with CRS-A to those with non-asthma-related CRS with (CRSwNP) and without nasal polyposis (CRSsNP). METHODS: Thirty-four patients with CRS-A (n=19) and CRS (n=15) were prospectively enrolled into an observational study. Demographic information and subjective and objective disease severity measures were recorded. Multiplex gene expression analysis of mRNA extracted from peripheral blood was performed. A total of 594 genes associated with innate/adaptive immunity were analyzed using NanoString technology. Gene expression ratios were reported for genes that were differentially expressed among these cohorts. Linear regression analysis was used to compare the mRNA transcript copy numbers for each gene with disease severity. RESULTS: There was no significant difference in age, gender, nasal polyposis, or health-related quality of life measures between the two groups (p>0.05). HLA class II histocompatibility antigen, DRB3-1 beta chain (HLA-DRB3) was significantly upregulated in the peripheral blood of patients with CRSsNP-A compared to CRSsNP, whereas chemokine (C-C motif) ligands 4 (CCL4) and zinc finger protein helios (IKZF2) were significantly upregulated in CRSwNP-A compared to CRSwNP (p<0.05). CONCLUSION: Patients with CRSsNP-A demonstrate a molecular endotype associated with a Th2-dominant inflammatory profile compared to CRSsNP. Patients with CRSwNP-A similarly demonstrate an overrepresentation of genes associated with Th2-driven inflammation compared to patients with CRSwNP.